2009
DOI: 10.1093/schbul/sbp096
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Childhood Trauma and Memory Functioning in Schizophrenia

Abstract: Childhood trauma is an important variable that can contribute to specific ongoing memory impairments in schizophrenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
77
3
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(91 citation statements)
references
References 43 publications
9
77
3
2
Order By: Relevance
“…Abuse and neglect are known to have a negative influence on cognitive functioning in community samples of healthy adults 20,21 and children/adolescents 22,23 as well as in patients with psychosis. 8,24,25 Congruent with other studies, [26][27][28] we have reported that children from densely affected multigenerational families who had a parent affected by schizophrenia or BD had fullscale IQ impairments as well as deficits in specific cognitive domains, such as visual and verbal episodic memory, working memory and executive functions of initiation. 12,16 These domains are among the most impaired in adult patients and are consistently found to be associated with schizophrenia and BD.…”
Section: Introductionsupporting
confidence: 55%
See 1 more Smart Citation
“…Abuse and neglect are known to have a negative influence on cognitive functioning in community samples of healthy adults 20,21 and children/adolescents 22,23 as well as in patients with psychosis. 8,24,25 Congruent with other studies, [26][27][28] we have reported that children from densely affected multigenerational families who had a parent affected by schizophrenia or BD had fullscale IQ impairments as well as deficits in specific cognitive domains, such as visual and verbal episodic memory, working memory and executive functions of initiation. 12,16 These domains are among the most impaired in adult patients and are consistently found to be associated with schizophrenia and BD.…”
Section: Introductionsupporting
confidence: 55%
“…Our hypothesis that childhood trauma would be responsible for the poor cognitive performance observed is supported by the literature, suggesting that childhood trauma leads to cognitive deficits. 8,[20][21][22][23][24][25] However, one might argue that cognitive deficits might increase the risk of maltreatment. Sixth, the present sample of 66 offspring was gathered from 25 of the 48 multigenerational families from the eastern Quebec catchment area; thus the representativeness of these 66 offspring with respect to those from the 23 other families would have to be confirmed.…”
Section: Limitationsmentioning
confidence: 99%
“…However, the extent to which the observed associations between neurocognitive functions and cortisol are triggered by psychosocial stress exposure is currently unclear. While some studies of individuals with schizophrenia have reported greater impairments in memory and executive function among those exposed to childhood maltreatment (Lysaker et al, 2001, Aas et al, 2011a, Shannon et al, 2011, Aas et al, 2012b, other studies have observed no association between psychosocial stress exposure (including childhood maltreatment) and neurocognitive deficits among individuals with psychosis (Schenkel et al, 2005, Aas et al, 2011c, Sideli et al, 2014. Indeed, Aas and colleagues reported that psychosocial stress exposure (childhood trauma, stressful life events, and perceived stress) was associated with poorer neurocognitive function among healthy individuals, but not among individuals with first-episode psychosis (Aas et al, 2011b), a finding that was replicated in a larger investigation of FEP patients in this study (Sideli et al, 2014).…”
Section: Stress Glucocorticoids and Cognitive Functionmentioning
confidence: 99%
“…Childhood maltreatment has been shown to affect cognitive performance in later life in previous studies of ostensibly healthy adults (Koenen et al, 2003, Pears et al, 2008, Perez and Widom, 1994, people with schizophrenia (Green et al, 2014, Lysaker et al, 2001, Shannon et al, 2009) and people diagnosed with borderline personality disorder (Afifi et al, 2011, Minzenberg et al, 2008. This study thus sought to further investigate potential interplay between four previously implicated genetic variants of FKBP5 (rs4713902, rs3800373, rs1360780, and rs9470080) and exposure to childhood maltreatment in relation to cognitive function (and symptom expression in patients) in a large sample of schizophrenia patients and healthy controls.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 96%